A rhamnose-deficient lipopolysaccharide mutant of Rhizobium sp. IRBG74 is defective in root colonization and beneficial interactions with its flooding-tolerant hosts Sesbania cannabina and wetland rice - Mitra, Shubhajit (Journal of experimental botany, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.